Pengaruh Simulasi Awal Data Pengamatan Terhadap Efektivitas Prediksi Pasang Surut Metode Admiralty (Studi Kasus Pelabuhan Dumai) - Rosmiati Ahmad; Andy Hendri; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This research to examines the initial variation of observation data based on Hijricalendar, because the initial time of observation data will affect the value of the resultingtidal components. The data was simulated against one hundred and thirty-five variationsof observation time. The result of data analysis shows that the smallest RMSE value fromthe verification result of the simulation data is found on the data of the early date of 12Hijri calendar is when the phase of the first humpback moon. This indicates that the timevariation of the date of the observation of the matching observation data at the study siteis between approaching the full moon phase and after the full moon phase. The F valueindicates that the location of the study entered on the classification of the daily doubletide type (semi diurnal tide).Keywords : tidal, method of Admiralty, Hijri